Global Warming Impact and Energy Analysis of Tempeh Made from Local and Imported Soybean - Muhamad Ifdholy; Muhammad Romli; Edi Wiloso (Indonesian Life Cycle Assessment Network (ILCAN), 2018)
AbstractIndonesia is a country with the largest number of tempeh producers in the world. However, the practice of tempeh production by most entrepreneurs has not paid enough attention to environmental aspects. In this study, Life Cycle Assessment (LCA) was used as a method to assess the environmental impact of tempeh labeled as hygienic, produced by Rumah Tempeh Indonesia (RTI) located in Bogor, West Java. The hygienic tempeh consists of two types, namely one made of local soybean (Tempeh Sehat) and the other made of imported soybean (Tempeh Kita). The extent of the environmental impact, in the form of GHG emissions and energy efficiency, throughout the life cycle of tempeh is calculated, analyzed and some improvement scenarios are proposed. The life cycle of tempeh is limited to soybean cultivation, raw material transportation and tempeh processing at RTI. The results show that Tempeh Sehat generates GHG emissions of 0.323 kg CO2-eq, while Tempeh Kita is 0.555 kg CO2-eq per kg of product. The hotspots that contribute to GHG impacts are identified as originating from the stages of soybeans transportation and tempeh processing. Energy efficiency is indicated by the Net Energy Value (NEV) and the Net Energy Ratio (NER) of both types of products. Tempeh Sehat has NEV of 2.064 MJ, while Tempeh Kita is 0.318 MJ. Both types of products show the value of NER>1. Further analysis of existing production practices has led to several scenarios of improvement and their environmental effects have been discussed. Keywords: Tempeh; LCA; GHG emission; energy efficiency